2022
DOI: 10.24996/ijs.2022.63.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin D Deficiency in Polycystic Ovarian Syndrome

Abstract: Polycystic ovary syndrome is a very common cause of female infertility. This study aims to assess the prevalence of vitamin D deficiency and its association with clinical and anthropometric characteristics of Iraqi women with and without polycystic ovary syndrome. Fifty eightwomen with the disease and their matched control group were included. Their blood pressure was measured. Serum level of 25 hydroxy vitamin D of <20 ng/mL was graded as vitamin D deficiency. The polycystic ovary syndrome group had signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The hepatic lipase's metabolism of these particles quickens when the Tg content of HDL rises [20].Additionally, the nature of LDL changes: there are more tiny, dense, oxidation-prone LDL particles, which leads to higher amounts of oxidized LDL and faster atherogenesis [21] [22].Endothelial dysfunction and the promotion of atherosclerosis are caused by a combination of low HDL, high small and dense LDL, hyperinsulinemia , hyperglycemia, and hypertriglyceridemia [23].Previous research has shown that 13% of AFM is attached to lipoproteins in the bloodstream, mostly to tiny, dense HDL particles but also to HDL that contains A1 apolipoprotein. Plasma lipoproteins contain 97% of the lipid-soluble and γ-tocopherol [24] [25]. But there are other proteins besides AFM that can also bind these γ-tocopherols selectively.…”
Section: Type 2 Diabetes Mellitus and Obesitymentioning
confidence: 99%
“…The hepatic lipase's metabolism of these particles quickens when the Tg content of HDL rises [20].Additionally, the nature of LDL changes: there are more tiny, dense, oxidation-prone LDL particles, which leads to higher amounts of oxidized LDL and faster atherogenesis [21] [22].Endothelial dysfunction and the promotion of atherosclerosis are caused by a combination of low HDL, high small and dense LDL, hyperinsulinemia , hyperglycemia, and hypertriglyceridemia [23].Previous research has shown that 13% of AFM is attached to lipoproteins in the bloodstream, mostly to tiny, dense HDL particles but also to HDL that contains A1 apolipoprotein. Plasma lipoproteins contain 97% of the lipid-soluble and γ-tocopherol [24] [25]. But there are other proteins besides AFM that can also bind these γ-tocopherols selectively.…”
Section: Type 2 Diabetes Mellitus and Obesitymentioning
confidence: 99%
“…Obesity is associated with greater myostatin expression, according to a number of studies 9,10 . Wild-type mice fed a high-fat diet for a month and genetically obese, leptin-deficient ob/ob mice both had increased skeletal muscle and fatty tissue myostatin mRNA levels 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Polycystic ovarian syndrome (PCOS) is a major cause of infertility in women (1). PCOS can have major repercussions, such as an increased chance of endometriosis and neoplasia (2).…”
Section: Introductionmentioning
confidence: 99%